2010
DOI: 10.2527/jas.2008-1698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with glutamine and a combination of glutamine-arginine on intestinal health in twenty-five-day-old weaned rabbits1

Abstract: The effect of dietary supplementation with 1% l-glutamine and a combination of 1% l-glutamine and 0.5% l-arginine on intestinal health was examined in weaned rabbits. A basal diet was formulated to meet nutrient recommendations. Another 2 diets were formulated by adding 1% (as-fed basis) Gln or a mixture of 1% (as-fed basis) Gln + 0.5% (as-fed basis) Arg (Gln-Arg) to the basal diet. In Exp. 1, a total of 357 rabbits were blocked by litter and assigned at random to the experimental diet to determine mortality (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 33 publications
7
58
3
4
Order By: Relevance
“…Little and contradictory data are available concerning the effect of the protein level on the intestinal mucosa traits in rabbits. Nor the changes in dietary CP concentration or the dietary supplementation with specific amino acids (glutamine and arginine; Chamorro et al, 2010), which may directly promote gastrointestinal integrity, modified mucosal histology of early-weaned rabbits. On the basis of current knowledge, we could hypothesise that the CP level and the concentration and characteristics of dietary fibre interact and modify both the amount of undigested protein reaching the caecum and the contribution of the endogenous nitrogen to the total ileal flux (García et al, 1995;Carabañ o et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Little and contradictory data are available concerning the effect of the protein level on the intestinal mucosa traits in rabbits. Nor the changes in dietary CP concentration or the dietary supplementation with specific amino acids (glutamine and arginine; Chamorro et al, 2010), which may directly promote gastrointestinal integrity, modified mucosal histology of early-weaned rabbits. On the basis of current knowledge, we could hypothesise that the CP level and the concentration and characteristics of dietary fibre interact and modify both the amount of undigested protein reaching the caecum and the contribution of the endogenous nitrogen to the total ileal flux (García et al, 1995;Carabañ o et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Gln under hypermetabolic states, including those which occur during weaning, is now firmly established Marc Rhoads and Wu, 2009). Dietary Gln supplementation prevents intestinal atrophy, and improves nutrient digestion and utilization in early weaning animals (Young and Ajami, 2001;Chamorro et al, 2010). Intestinal microbiota and blood amino acid concentrations were modified by Gln treatment in postweaned animals (Wu et al, 1996;Chamorro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed Gln playing an essential role in early weaned animals (Wu et al, 1996;Wang et al, 2008;Chamorro et al, 2010). In the current study, dietary Gln supplementation increased the serum concentrations of creatinine, palmitelaidic acid, D-xylose, α-L-galactofuranose, and 2-hydroxybutanoic acid.…”
Section: Fig 7 Kegg Pathways Linked Together Manuallymentioning
confidence: 99%
See 1 more Smart Citation
“…and Clostridium spp. in ileum of rabbits [39]. Moreover, our laboratory studies showed some amino acids such as methionine [40], histidine [8] and valine [9] affect microbial population in the intestine of Jian carp.…”
Section: Introductionmentioning
confidence: 99%